Telitacicept in myasthenia gravis: a systematic review of clinical outcomes, steroid-sparing effects, and safety - Weitong Zhang; Yue Wang; Wenjun Qiao (Frontiers in Neurology, 2026)
Introduction Myasthenia gravis (MG) is an antibody-mediated autoimmune neuromuscular disorder for which long-term disease control remains challenging in some patients. Telitacicept, a dual inhibitor of B-cell activating factor (BAFF) and a proliferation-inducing ligand (APRIL), has been investigated as a potential therapeutic option for MG. This systematic review aimed to evaluate the clinical efficacy, steroid-sparing effects, and safety profile of telitacicept in patients with MG. Methods A comprehensive search of PubMed, Scopus, Web of Science Core Collection, Embase, Cochrane Central Register of Controlled Trials (CENTRAL), China National Knowledge Infrastructure (CNKI), and Wanfang Data was conducted from database inception to January 19, 2026. Studies reporting clinical outcomes of telitacicept in MG were included. Two reviewers independently performed study selection, data extraction, and risk-of-bias assessment. Due to substantial heterogeneity in study designs, patient populations, treatment strategies, and outcome measures, a qualitative synthesis was performed. Results Fifteen studies, including one randomized phase II trial, four retrospective cohort studies, one retrospective comparative study, four case series, and five case reports, were included. Available evidence generally suggested improvements in disease severity measures, particularly reductions in Quantitative Myasthenia Gravis (QMG) and Myasthenia Gravis Activities of Daily Living (MG-ADL) scores. In the randomized phase II trial of generalized MG, QMG decreased by approximately 7–10 points at 24 weeks, with response rates exceeding 90%. Several observational studies also reported reductions in glucocorticoid requirements. Adverse events were generally mild and transient, although the interpretation of long-term safety was limited by small sample sizes and short follow-up durations. Discussion Current evidence suggests that telitacicept may provide potential clinical benefits and steroid-sparing effects in selected patients with MG. However, the certainty of evidence remains limited because most available studies were retrospective or uncontrolled, and further well-designed randomized controlled trials are required to establish its efficacy, long-term safety, and optimal clinical positioning.